Misoprostol as an Adjunct to Standard Uterotonics for Treatment of Post-Partum Haemorrhage : A Multicentre, Double-Blind Randomised Trial - Widmer, M. (2012)
BACKGROUND: Post-partum haemorrhage is a leading cause of global maternal morbidity and mortality. Misoprostol, a prostaglandin analogue with uterotonic activity, is an attractive option for treatment because it is stable, active orally, and inexpensive. We aimed to assess the effectiveness of misoprostol as an adjunct to standard uterotonics compared with standard uterotonics alone for treatment of post-partum haemorrhage. METHODS: Women delivering vaginally who had clinically diagnosed post-partum haemorrhage due to uterine atony were enrolled from participating hospitals in Argentina, Egypt, South Africa, Thailand, and Vietnam between July, 2005, and August, 2008. Computer-generated randomisation was used to assign women to receive 600 microg misoprostol or matching placebo sublingually; both groups were also given routine injectable uterotonics. Allocation was concealed by distribution of sealed and sequentially numbered treatment packs in the order that women were enrolled. Providers and women were masked to treatment assignment. The primary outcome was blood loss of 500 mL or more within 60 min after randomisation. Analysis was by intention to treat. This study is registered, number ISRCTN34455240. FINDINGS: 1422 women were assigned to receive misoprostol (n=705) or placebo (n=717). The proportion of women with blood loss of 500 mL or more within 60 min was similar between the misoprostol group (100 [14%]) and the placebo group (100 [14%]; relative risk 1.02, 95% CI 0.79-1.32). In the first 60 min, an increased proportion of women on misoprostol versus placebo, had shivering (455/704 [65%] vs 230/717 [32%]; 2.01, 1.79-2.27) and body temperature of 38 degrees C or higher (303/704 [43%] vs 107/717 [15%]; 2.88, 2.37-2.50). INTERPRETATION: Findings from this study do not support clinical use of 600 microg sublingual misoprostol in addition to standard injectable uterotonics for treatment of post-partum haemorrhage. FUNDING: Bill & Melinda Gates Foundation, and UNDP/UNFPA/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction.